2013
DOI: 10.1016/j.enggeo.2012.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Mountain torrents: Quantifying vulnerability and assessing uncertainties

Abstract: Vulnerability assessment for elements at risk is an important component in the framework of risk assessment. The vulnerability of buildings affected by torrent processes can be quantified by vulnerability functions that express a mathematical relationship between the degree of loss of individual elements at risk and the intensity of the impacting process. Based on data from the Austrian Alps, we extended a vulnerability curve for residential buildings affected by fluvial sediment transport processes to other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(76 citation statements)
references
References 37 publications
4
72
0
Order By: Relevance
“…As far as debris flow is concerned, the first approaches for physical vulnerability assessment were qualitative (Fell and Hartford, 1997;Liu and Lei, 2003;Romang, 2004), including in some cases vulnerability matrices (Leone et al, 1995(Leone et al, , 1996Sterlacchini et al, 2007;Zanchetta et al, 2004) showing a descriptive relationship between the damage and intensity of the flow. However, recently the number of vulnerability curves for debris flows has considerably increased and several studies may be found in the literature Papathoma-Köhle et al, 2012;Quan Luna et al, 2011;Totschnig and Fuchs, 2013;Totschnig et al, 2011). Each vulnerability curve has been developed for a specific area, is based on a particular catastrophic event and expresses the intensity of the process in various ways.…”
Section: Methods For Assessing Physical Vulnerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…As far as debris flow is concerned, the first approaches for physical vulnerability assessment were qualitative (Fell and Hartford, 1997;Liu and Lei, 2003;Romang, 2004), including in some cases vulnerability matrices (Leone et al, 1995(Leone et al, , 1996Sterlacchini et al, 2007;Zanchetta et al, 2004) showing a descriptive relationship between the damage and intensity of the flow. However, recently the number of vulnerability curves for debris flows has considerably increased and several studies may be found in the literature Papathoma-Köhle et al, 2012;Quan Luna et al, 2011;Totschnig and Fuchs, 2013;Totschnig et al, 2011). Each vulnerability curve has been developed for a specific area, is based on a particular catastrophic event and expresses the intensity of the process in various ways.…”
Section: Methods For Assessing Physical Vulnerabilitymentioning
confidence: 99%
“…Efforts to analyse and quantify uncertainties concerning the assessment of physical vulnerability for debris flows have been made in the past (Eidsvig et al, 2014;Totschnig and Fuchs, 2013); however, most of them concern vulnerability curves. Based on the comparison of the two methods and the outline of the advantages and disadvantages of it as far as the assessment of physical vulnerability is concerned a number of recommendations for improvement may be made.…”
Section: Cost Effectivementioning
confidence: 99%
“…Nevertheless, for larger mountain rivers like the Austrian Lech River no study analyzed the general applicability of flood damage models so far as previous investigations aimed mainly on dynamic floods of steep torrent streams (see Totschnig and Fuchs, 2013 for an overview). Hence, it is still an open question to which extent depth-damage functions which are mainly developed for lowland areas can be applied in mountainous regions where floods are characterized by a more dynamical impact.…”
Section: Introductionmentioning
confidence: 99%
“…Others relied on model intercomparisons (e.g., Bubeck et al, 2011; but did not validate the model performance with real damage data. In the case of mountainous areas, flood loss estimation was only validated for torrent processes (e.g., Totschnig and Fuchs, 2013) but no study addressed larger mountain rivers so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation